Research Mapping of Technology Adoption & Acceptance Models in Business: A Literature Study - Suhaji, Ichwan Wahyu (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This paper aims to describe the development of technology and system adoption and acceptance research model. We specified our meta-analysis work on the amount of research regarding technology adoption and acceptance in business context. We generated 20 articles which were published in Multidisciplinary Digital Publishing Institute (MDPI) for the current year, 2023. Hereafter, these articles were classified based on research topics, theories, methods, and models used by the authors. Based on journal source map, research related to adoption & acceptance of technology is dominated by articles from sustainability journal source. Technology Acceptance Model (TAM) was the dominant theoretical framework that has been used. Furthermore, four elements of UTAUT model namely performance expectancy, effort expectancy, social influence, and facilitating conditions are most considerable predictors in current year research. Structural model to predict behavioural intention on technology in business was dominantly examined. This article review uncovered several gaps from previous research in those areas. Further research can do the experimental research project, mixed-method, and examined the continuance intention which still has small attention. Finally, the UTAUT 3 that has been introduced in this literature review is worthy to test in future research.